Peculiarities of Adverse Events Manifested by Injury of Skin and Skin Derivatives and Associated with Beta-blockers Use - A. V. Matveev; E. A. Egorova; E. I. Konyaeva; A. G. Dormidor; E. Yu. Bekirova (Столичная издательская компания, 2021)
More than 50 years after Propranolol was introduced to the pharmaceutical market as a drug that can lower the heart rate, beta-blockers (BAB) are still widely used in the pharmacotherapy of cardiovascular diseases. However, the use of BAB has a number of limitations, first of all, due to adverse drug events (AE) that develop during their use. The purpose of our review was to study the features of the BAB AE manifested by injuries of the skin and its appendages. The clinical manifestations of them are the development or exacerbation of psoriasis, lichen planus, contact dermatitis, acrocyanosis, Raynaud's disease, alopecia, hyperhidrosis, vitiligo, anaphylaxis, and allergic skin reactions. True medicinal psoriasis occurs in patients taking BAB with no family or previous history and most often mimics erythrodermic psoriasis and palmar-plantar pustular psoriasis. Systemic use of BAB can also be accompanied by exacerbation of vitiligo. In patients with segmental vitiligo, the results of Doppler flowmetry and iontophoresis showed increased blood flow in vitiligo foci compared with normal skin. The development of anaphylactic reactions against the background of BAB therapy may be due to the modulation of adenylate cyclase, which can affect the release of anaphylactogenic mediators, as well as a decrease in the severity of cardiovascular compensatory changes. The peculiarities of the development of such reactions may be the resistance of patients to traditional treatment, which is due to the development of paradoxical reflex vagotonic effects when using adrenaline. Some of the mentioned AE may pose a potential threat to the life and health of the patient and therefore require additional discussion.